Pengaruh Pengutipan Minyak Ex-Empty Bunch Press terhadap Kadar Free Fatty Acid (FFA) Minyak Produksi (Studi Kasus PT Sawindo Kencana, Bangka Belitung) - Azhar Basyir Rantawi; Ahdiat Leksi Siregar; . Zaitun (JURNAL CITRA WIDYA EDUKASI, 2019)
This reserach purpose to determine the FFA level of production oil when blending with oil from the recovery tank which is the result of blending ex-empty bunch press and fat pit oil. The solution to the problem that arises due to the condition of the FFA is to find an alternative solution, which is to drain the ex-empty bunch press oil in the temporary reservoir. The result showed that the oil FFA content of the production when blending with oil from the recovery tank was 4.72%; while the oil FFA from the recovery tank was 16.22%. FFA levels in the production oil can be reduced to 3.04% after repairs to the ex-empty bunch press oil citation system.